Identifying the most important factors of stability and instability in the villages of Zarrin Dasht county - Mohsen Shayan; Sirous ghanbari; Javad Bazrafshan (کاوش‌های جغرافیایی مناطق بیابانی, 2021)
Today, sustainability and instability is one of the rural challenges. Therefore, the purpose of this study is to identify the most important factors of sustainability and instability in the villages of Zarrin Dasht County.The present research is applied in terms of purpose and descriptive-analytical in terms of method of work. The statistical population of the study consists of the villages of Zarrin Dasht county, which according to the general census of 2016 was 7927 households. Cochran's formula was used to select the sample size. In this study, 310 heads of households were selected as a sample. The method of selecting the sample villages was regular classification and the method of completing the questionnaires was simple random. The validity of the questionnaire has been confirmed by experts and university professors and Cronbach's alpha coefficient has been used to determine the reliability of the research. The calculated alpha value is 77.5 which indicates that it is a desirable number and the accuracy required to determine the reliability of the structures used in the questionnaire and the items designed to measure the indicators are internally correlated. Exploratory factor analysis test was used to analyze the research findings. The results showed that 7 factors of economic, social, managerial, infrastructure, health and environmental hazards are the most important factors of sustainability and instability in the villages of Zarrin Dasht, respectively. Also, the results showed that weakness in the mentioned factors, especially economic and social factors, is directly related to the instability of rural settlements.Today, sustainability and instability is one of the rural challenges. Therefore, the purpose of this study is to identify the most important factors of sustainability and instability in the villages of Zarrin Dasht County.The present research is applied in terms of purpose and descriptive-analytical in terms of method of work. The statistical population of the study consists of the villages of Zarrin Dasht county, which according to the general census of 2016 was 7927 households. Cochran's formula was used to select the sample size. In this study, 310 heads of households were selected as a sample. The method of selecting the sample villages was regular classification and the method of completing the questionnaires was simple random. The validity of the questionnaire has been confirmed by experts and university professors and Cronbach's alpha coefficient has been used to determine the reliability of the research. The calculated alpha value is 77.5 which indicates that it is a desirable number and the accuracy required to determine the reliability of the structures used in the questionnaire and the items designed to measure the indicators are internally correlated. Exploratory factor analysis test was used to analyze the research findings. The results showed that 7 factors of economic, social, managerial, infrastructure, health and environmental hazards are the most important factors of sustainability and instability in the villages of Zarrin Dasht, respectively. Also, the results showed that weakness in the mentioned factors, especially economic and social factors, is directly related to the instability of rural settlements.Today, sustainability and instability is one of the rural challenges. Therefore, the purpose of this study is to identify the most important factors of sustainability and instability in the villages of Zarrin Dasht County.The present research is applied in terms of purpose and descriptive-analytical in terms of method of work. The statistical population of the study consists of the villages of Zarrin Dasht county, which according to the general census of 2016 was 7927 households. Cochran's formula was used to select the sample size. In this study, 310 heads of households were selected as a sample. The method of selecting the sample villages was regular classification and the method of completing the questionnaires was simple random. The validity of the questionnaire has been confirmed by experts and university professors and Cronbach's alpha coefficient has been used to determine the reliability of the research. The calculated alpha value is 77.5 which indicates that it is a desirable number and the accuracy required to determine the reliability of the structures used in the questionnaire and the items designed to measure the indicators are internally correlated. Exploratory factor analysis test was used to analyze the research findings. The results showed that 7 factors of economic, social, managerial, infrastructure, health and environmental hazards are the most important factors of sustainability and instability in the villages of Zarrin Dasht, respectively. Also, the results showed that weakness in the mentioned factors, especially economic and social factors, is directly related to the instability of rural settlements.Today, sustainability and instability is one of the rural challenges. Therefore, the purpose of this study is to identify the most important factors of sustainability and instability in the villages of Zarrin Dasht County.The present research is applied in terms of purpose and descriptive-analytical in terms of method of work. The statistical population of the study consists of the villages of Zarrin Dasht county, which according to the general census of 2016 was 7927 households. Cochran's formula was used to select the sample size. In this study, 310 heads of households were selected as a sample. The method of selecting the sample villages was regular classification and the method of completing the questionnaires was simple random. The validity of the questionnaire has been confirmed by experts and university professors and Cronbach's alpha coefficient has been used to determine the reliability of the research. The calculated alpha value is 77.5 which indicates that it is a desirable number and the accuracy required to determine the reliability of the structures used in the questionnaire and the items designed to measure the indicators are internally correlated. Exploratory factor analysis test was used to analyze the research findings. The results showed that 7 factors of economic, social, managerial, infrastructure, health and environmental hazards are the most important factors of sustainability and instability in the villages of Zarrin Dasht, respectively. Also, the results showed that weakness in the mentioned factors, especially economic and social factors, is directly related to the instability of rural settlements.